Impact of Secukinumab on Patient-Reported Outcomes in the Treatment of Ankylosing Spondylitis: Current Perspectives - Tahir H (Dove Medical Press, 2020)
Hasan Tahir,1,2 Arumugam Moorthy,3 Antoni Chan4 1Royal Free London NHS Trust, London, UK; 2Division of Medicine, University College London, London, UK; 3University Hospitals of Leicester NHS Trust, Leicester, UK; 4Royal Berkshire NHS Trust, Reading, UKCorrespondence: Hasan TahirRoyal Free London NHS Trust, London, UKEmail hasan.tahir@nhs.netAbstract: Ankylosing spondylitis (AS) is a chronic rheumatic disease involving inflammation of the joints and spine, which carries a substantial, life-long burden for the patient. Secukinumab is a fully human anti-interleukin-17A monoclonal antibody, approved in the USA and EU for the treatment of AS. In this narrative review, we searched PubMed with the aim of consolidating the recent literature regarding the impact of secukinumab on patient-reported outcomes in patients with AS. A large clinical trial program has demonstrated the efficacy of secukinumab in relieving the signs and symptoms of AS. Most importantly from a patient perspective, secukinumab has produced improvements in a range of patient-reported outcomes (PROs), including pain, fatigue, quality of life and work productivity, as well as composite measures including patient-reported elements, such as the Bath indices and Assessment of SpondyloArthritis international Society (ASAS) response criteria. Benefits to patients were rapid, and sustained in the long term (up to 5 years). The positive effect of secukinumab was seen regardless of whether patients had previously been treated with anti-tumor necrosis factor (TNF) therapies. Greater improvements in PROs were associated with patients being anti-TNF-naïve, of a younger age, with shorter disease duration and higher objective measures of inflammation at baseline. The available real-world evidence suggests that the effects of secukinumab on PROs in clinical practice are consistent with those seen in clinical trials, and evidence in a real-world setting continues to be collected.Keywords: ankylosing spondylitis, secukinumab, patient-reported outcomes